2022
DOI: 10.1093/mnras/stac2229
|View full text |Cite|
|
Sign up to set email alerts
|

The formation of early-type galaxies through monolithic collapse of gas clouds in Milgromian gravity

Abstract: Studies of stellar populations in early-type galaxies (ETGs) show that the more massive galaxies form earlier and have a shorter star formation history (SFH). In this study, we investigate the initial conditions of ETG formation. The study begins with the collapse of non-rotating post-Big-Bang gas clouds in Milgromian (MOND) gravitation. These produce ETGs with star-forming timescales (SFT) comparable to those observed in the real Universe. Comparing these collapse models with observations, we set constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…It is already well established that Milgromian gravitation correctly accounts for the properties of elliptical galaxies (Eappen et al 2022;Eappen & Kroupa 2024), and of disk galaxies (e.g. Famaey & McGaugh 2012;Banik & Zhao 2022;specific 2024) all find it to be decreasing over this distance range by about 30 km/s being consistent with a Keplerian decline.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is already well established that Milgromian gravitation correctly accounts for the properties of elliptical galaxies (Eappen et al 2022;Eappen & Kroupa 2024), and of disk galaxies (e.g. Famaey & McGaugh 2012;Banik & Zhao 2022;specific 2024) all find it to be decreasing over this distance range by about 30 km/s being consistent with a Keplerian decline.…”
Section: Discussionmentioning
confidence: 55%
“…Solutions without dark matter particles but with Milgromian potentials are readily obtained though. Noteworthy in this context is that earlier work had already shown that the observed rotation curves of disk galaxies cannot be reproduced if the theoretically-predicted dark matter halos are assumed (McGaugh 2005;McGaugh et al 2007), and elliptical galaxies take too long to assemble in the dark-matter-based structure formation models to be consistent with their rapid early formation (Eappen et al 2022). Independently of the above results concerning Milgromian dynamics, these tests thus suggest that dark matter particles do not exist.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, the present findings can also imply that structure formation is much more efficient and/or that the observed universe is even older than predicted by ΛCDM. The existence of these massive galaxies ≈300-400 Myr after the Big Bang also questions the hierarchical (bottom-up) structure formation suggesting that late-type galaxies begin to form early through the initial monolithic collapse of rotating post-Big-Bang gas clouds (Wittenburg et al 2020) while early-type massive galaxies and associated formation of supermassive black halos form by the monolithic collapse of post-Big-Bang gas clouds with little net rotation (e.g., Kroupa et al 2020b;Wittenburg et al 2020;Yan et al 2021;Eappen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(T5) The downsizing time-scales of the rapid formation of elliptical galaxies arise naturally from initial non-rotating gas clouds (Eappen et al 2022 [99]). Sub-grid physics describing star formation and gas heating and cooling are not critical for these outcomes (Wittenburg 2020 [68], Eappen et al 2022 [99], Nagesh et al 2023 [213]) such that cosmological structure formation simulations in Milgromian dynamics of a largely baryonic universe with galaxy-scale resolution are expected to lead to a population of galaxies that should have the correct properties. The rapid formation of spheroids (bulges, elliptical galaxies) produces the exact environment in which SMBHs form naturally and fast (Kroupa et al 2020 [103]), while the rarity of mergers leaves these at the centres of their hosting galaxies as observed (Lena et al 2014 [102]).…”
Section: Pos(corfu2022)231mentioning
confidence: 99%